CLUSTERING KELOMPOK BELAJAR SISWA BERDASARKAN HASIL UJIAN SEKOLAH MENGGUNAKAN ALGORITMA K-MEANS - Mohammad Syaefudulloh; Ahmad Faqih; Fadhil Muhammad Basysyar (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Introduction: The government has the responsibility of determining national education quality policies and standards and has a role to evaluate the implementation of education in the framework of national education quality control. One way to evaluate the standards of primary and secondary education nationally is the results of the achievement of the National Examination (UN). The quality of students in learning in schools has a lot of diversity this makes students have different levels of understanding this can be seen from the variety of school test scores obtained, this needs to be a concern for the school, especially teachers. One of them is by forming an effective study group so that every student has the opportunity to excel. To find out how to cluster the quality of Astanajapura State High School education based on the results of school test scores. Method: Research conducted using machine learning with K-Means algorithm with sample datasets or secondary data from State High School 1 Astanajapura Class XII which will be used as the material of this study. Method: Research conducted using machine learning with K-Means algorithm with sample datasets or secondary data from State High School 1 Astanajapura Class XII which will be used as the material of this study. Results: The results in this study get a cluster of students, namely students are very prestigious, prestigious and less prestigious. The clustering obtained in this study k = 4 is that there are 145 students categorized into cluster 0 with a DBi value of 0.763. The evaluation results of the K-Means algorithm resulted in a cluster with excellent and good grades, the results of this study can be used as a guideline for teaching teachers in decision making on the formation of student learning groups in Class XII. Discussion: The use of the K-Means method to group is one of the appropriate methods when viewed from the variables to be used, namely school test scores